Astronomy Modeling Training for Science Teachers in Grobogan District: Implementation of Planetarium and Observatory-Based Education - Ahmad Syifaul Anam; Irman Said Prastyo; Wali Cosara; Mutiara Tembang Langit; Muhammad Said Fadhel; Muhammad Afan Nur Atqiya; Fika Afhamul Fuscha; Khotibul Umam; Ikhsan Mahaendra; Muhammad Adam; Muhammad Hasan Fizna Hadil Wafa (Community Research and Application Journal (CRAJ), 2025)
Effective astronomy education requires hands-on experience with modern technological tools and observational practices. This community service project aimed to enhance the pedagogical competencies of science teachers from the Science Teacher Working Group (MGMP IPA) of Grobogan District through comprehensive training in astronomy modeling and observation techniques. The training, conducted on July 17, 2025, at the Planetarium and Observatory of Universitas Islam Negeri Walisongo Semarang, integrated theoretical knowledge with practical applications using professional software and instruments. Participants engaged in interactive seminars featuring astronomical modeling through web-based simulations and specialized software including Stellarium, SpaceEngine, and Cartes du Ciel. The program also included immersive planetarium experiences with 4K dome visualization and hands-on telescope observation sessions. Feedback from 32 participating teachers indicated high satisfaction levels and increased confidence in implementing astronomy education in their classrooms. The collaboration between the educational institution and the teacher working group proved effective in bridging the gap between theoretical astronomy knowledge and practical teaching methodologies. This initiative highlights the critical role of planetariums and observatories in supporting STEM education and suggests the need for continued professional development programs for science educators.